2004
DOI: 10.1074/jbc.m404748200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Epitope in the Thyroid-stimulating Hormone Receptor Ectodomain Acting as Intramolecular Signaling Interface

Abstract: Glycoprotein hormone receptors (GPHRs) differ from the other seven transmembrane receptors mainly through a complex activation mechanism that requires the binding of a large hormone toward a large N-terminal ectodomain. The intramolecular mechanism of the signal transduction to the serpentine domain upon hormone binding at the ectodomain is not understood. To identify determinants at the GPHR ectodomain that may be involved in signal transduction, we first searched for homologous structural features. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…Some theoretical models of the TSH-TSHR complex (Kleinau et al 2004, Moyle et al 2004, Nú ñez Miguel et al 2004 were published just before the coordinates of the FSH-FSHR complex became available (Fan & Hendrickson 2005). The structure of the concave surface and b-strands of the TSHR LRD were well defined in the three models (Kleinau et al 2004, Moyle et al 2004, Nú ñez Miguel et al 2004.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some theoretical models of the TSH-TSHR complex (Kleinau et al 2004, Moyle et al 2004, Nú ñez Miguel et al 2004 were published just before the coordinates of the FSH-FSHR complex became available (Fan & Hendrickson 2005). The structure of the concave surface and b-strands of the TSHR LRD were well defined in the three models (Kleinau et al 2004, Moyle et al 2004, Nú ñez Miguel et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the concave surface and b-strands of the TSHR LRD were well defined in the three models (Kleinau et al 2004, Moyle et al 2004, Nú ñez Miguel et al 2004. The model of Moyle et al (2004) comprised three domains of the TSHR linked together and the LRD structure was modelled on the structure of ubiquitin ligase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is established that the C-b2 and 3 potentially interact via disulfide bonds (21)(22)(23) and that mutations disrupting the disulfide bridge lead to constitutive activation (24,25). In a previous study we identified new residues within C-b3 that are also involved in receptor stabilization and intramolecular signal transduction based on a suggested homologous molecular model for the C-b2/C-b3 unit (26). By site-directed mutagenesis we defined a region (Asp-403 Glu-404 Asn-406) of the TSHR ectodomain that can act as a switch for constitutive activity.…”
mentioning
confidence: 99%